PETROLEUM FUND PADA PEMERINTAHAN LOKAL (STUDY KASUS INOVASI KEBIJAKAN â€œDANA ABADI MIGASâ€ DI BOJONEGORO) - Sholikin, Ahmad (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The Bojonegoro District Government took the initiative to establish the Bojonegoro Petroleum and Natural Gas (Oil and Gas) Endowment Fund. The establishment of this Oil and Gas Endowment Fund aims to ensure the existence of a saving fund for future generations when oil and gas and gas in the region has run out. This idea is in line with the fact that in the long term Bojonegoro will contribute significantly to domestic oil and gas production and also the fact that Bojonegoro has succeeded in alleviating poverty, in one area that was once considered the poorest district in Java. The establishment of the Oil and Gas Endowment Fund is also based on consideration of avoiding the curse of natural resources. Reflecting on the experience of regions rich in natural resources, including oil and gas resources, where the level of human welfare and development is lower than in areas of poor natural resources. The level of social conflict is quite high, environmental damage is quite severe, Dutch desiase, excessive spending (over spending), corruption thrives and more.